A Descriptive study of digit-gambling in Barangay Poblacion, Compostela, Compostela Valley Province - Hermosilla, Janice C.
This is a descriptive study of the nature and dynamics of digit-gambling in Brgy. Poblacion, Compostela, Compostela Valley Province. This study provides a descriptive of digit-gambling as an existing activity in the municipality as well as the relationship of the participants involved. The objectives of the study are: (1) to describe the activities that happen in this game and to list words or teminologies used in digit-gambling; (2) to gather the reasons of particular individuals who bet; and (3) to characterize the people involved in this gambling game and the specific roles and functions that they portray as part of the activity. The study also used both the qualitative and quantitative methods in gathering the data and information needed. It used the survey method in gathering the personal profile of the respondents. Tabulation and computation of percentages were also used to organize the data gathered from the survey. Participant observation method was done and formal and informal interviews with the key informants were conducted. The tayador, ushers, coordinators, and financiers are the major actors of the digit game. Besides, the presence of the authorities in digit-gambling suggests what kind of role the government portrays. Moreover, digit-gambling is perceived by the respondents as a source of income and also provides them leisure and fun. Basically, digit-gambling is a form of recreation for the participants involved in the gambling game. It also provides added income and employment that are relevant in the economic condition of the municipality. Furthermore, the study provides the list of words or terminologies used in digit-gambling as well as the activities that happen within the activity. The study also revealed that the existence of digit-gambling in Compostela is only beneficial to the few most especially to the financiers. On the other hand, it is disadvantageous on the part of the tayador because they are just taking the chances of winning by betting numbers without the assurance of a sure win or a big profit.